Association between metabolic score for visceral fat and psoriasis: findings from NHANES - Xinyi Shao; Yi Ou; Qian Liu; Yidian Fu; Yan Pan; Aijun Chen; Genlong Bai; Jingbo Zhang (European Journal of Medical Research)
Abstract Background Psoriasis is a persistent inflammatory skin condition. Several studies have revealed that obesity significantly contributes to both the initiation and advancement of psoriasis. The metabolic score for visceral fat (METS-VF) represents an innovative measure designed to forecast visceral obesity, integrating factors such as insulin resistance metabolic score, waist-to-hip ratio (WHR), age, and gender. The present study aimed to investigate the association between METS-VF and psoriasis prevalence, using information gathered from the National Health and Nutrition Examination Survey (NHANES). Methods This study utilized the data from a nationally representative cohort of 8023 adults from NHANES from 2003–2006 to 2009–2014, of which 234 declared a psoriasis history. Multivariate logistic regression analysis and restricted cubic spline (RCS) analyses were used to investigate the association between METS-VF and psoriasis, followed by subgroup analysis to identify populations that may exhibit higher sensitivity. Results After adjusting for confounding variables, the results of the multivariate logistic regression analysis showed a significant positive association between METS-VF and the risk of psoriasis. One-unit increasement in METS-VF corresponded to a 47% rise in psoriasis risk (odds ratio [OR] = 1.47, 95% confidence interval [CI] = 1.10–1.96). Finally, the results were uniform across all subgroups (P for interaction > 0.05). The results from the RCS analysis indicated a notable linear association. Conclusion This research indicated that elevated levels of METS-VF are linked to a higher occurrence of psoriasis, suggesting the potential of METS-VF as a predictive anthropometric index for assessing the risk of developing psoriasis.